Using Platelet-Rich Fibrin to Remove Graphite Tattoos May Yield Excellent Long-Term Result - Young Joon Cho; Yong Tak Jeong; Tae Hee Lee; Hyun Woo Cho (Case Reports in Dentistry)
Graphite tattoos are rarely reported because they are mainly caused by an accidental injury or habits during childhood that cause a pencil to penetrate the oral mucosa. Unlike other pigmentations, it stains layers that are deeper than the subepithelial and mucosal layers, and in most cases, it takes the form of a grayish black macule. This case report describes depigmentation with the denudation technique that was followed by a novel approach of using platelet-rich fibrin to cover exposed bone. A 41-year-old male patient presented with an aesthetic complaint from a grayish black staining on the labial gingiva near the maxillary central and lateral incisors. The lesion was diagnosed as a graphite tattoo due to the patient’s history of sticking his gum with pencils when he was young. The entire pigmented gingiva was surgically removed and covered with two layers of PRF membrane to protect the exposed bone surface and provide an extracellular matrix for migration of gingival fibroblasts. Healing patterns were observed at 1, 2, 4, and 8 weeks, and satisfactory clinical and aesthetic results were obtained. Creeping attachment was observed at 8 years postop, and there was no recurrence for a long-term period of 13 years.